A 3D measurement of the offset in paleoseismological studies - Ferrater, Marta; Echeverria, Anna; Masana, Eulàlia; Martínez-Díaz, José J.; Sharp, Warren D. (Computers & geosciences, 2016)
The slip rate of a seismogenic fault is a crucial parameter for establishing the contribution of the fault to the seismic hazard. It is calculated from measurements of the offset of linear landforms, such channels, produced by the fault combined with their age. The three-dimensional measurement of offset in buried paleochannels is subject to uncertainties that need to be quantitatively assessed and propagated into the slip rate. Here, we present a set of adapted scripts to calculate the net, lateral and vertical tectonic offset components caused by faults, together with their associated uncertainties. This technique is applied here to a buried channel identified in the stratigraphic record during a paleoseismological study at the El Saltador site (Alhama de Murcia fault, Iberian Peninsula). After defining and measuring the coordinates of the key points of a buried channel in the walls of eight trenches excavated parallel to the fault, we (a) adjusted a 3D straight line to these points and then extrapolated the tendency of this line onto a simplified fault plane; (b) repeated these two steps for the segment of the channel in the other side of the fault; and (c) measured the distance between the two resulting intersection points with the fault plane. In doing so, we avoided the near fault modification of the channel trace and obtained a three-dimensional measurement of offset and its uncertainty. This methodology is a substantial modification of previous procedures that require excavating progressively towards the fault, leading to possible underestimation of offset due to diffuse deformation near the fault. Combining the offset with numerical dating of the buried channel via U-series on soil carbonate, we calculated a maximum estimate of the net slip rate and its vertical and lateral components for the Alhama de Murcia fault. •The proposed methodologic approach modifies 3D paleoseismologic existing techniques.•The offset of a buried channel is measured projecting its tendency into the fault.•The calculated maximum net slip rate for Alhama de Murcia fault is 1.3 +0.2/–0.1mm/yr.